Preparation method of high-temperature-resistant supercapacitor based on GaN as electrode material
Directly forming a patterned gallium nitride film through photolithography technology, solving the problem of degradation in existing supercapacitors in high temperature environments, simplifying the preparation process, and improving production efficiency and stability.
Patent Information
- Application Number
- CN202411698721.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
Existing supercapacitors have degraded or failed performance in high temperature environments, and the preparation process is complex, resulting in high production costs and low efficiency.
The Si sheet epitaxial gallium nitride is processed through photolithography to form a high-resolution patterned gallium nitride film, which directly forms the cathode and anode of the supercapacitor, simplifying the electrode preparation process.
The normal operation of the capacitor in a high temperature environment is achieved, the complexity and cost of the electrode preparation process is reduced, and the production efficiency and device stability are improved.
Smart Images

Figure CN119480471A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of semiconductor devices, and in particular relates to a method for preparing a supercapacitor, which can be used for electronic equipment in a high-temperature environment. Background Art
[0002] With the rapid advancement of science and technology, supercapacitors, as an efficient and environmentally friendly energy storage device, have been increasingly widely used, covering multiple key fields such as electric vehicles, aerospace, military equipment, and industrial control. These fields not only require supercapacitors to have basic properties such as high energy density, high power density, and long cycle life, but also place extremely high demands on their stability in high temperature environments. Taking electric vehicles as an example, in hot summer or after long periods of high-speed driving, vehicles may face the challenge of high temperature environments. If the supercapacitor cannot withstand such high temperatures, its performance will be greatly reduced, which will in turn affect the range, acceleration performance, and even overall safety of the electric vehicle. Therefore, developing high-temperature resistant supercapacitors to ensure that they can still work stably under extreme conditions has become the key to improving the comprehensive performance of equipment in these fields.
[0003] It is worth noting that although lithium-ion batteries occupy a large part of the electronic product market, safety remains a key issue in high-temperature environments due to the flammability of organic reagents and the risk of electrolyte leakage. For example, the temperature of uninterruptible power supply UPS exceeds 100°C, and the temperature of medical-grade sterilization equipment is at least 120°C. Most electrolytes in commercial organic batteries are prone to decomposition or volatilization in high-temperature environments because their boiling points are usually below 80°C, resulting in battery performance degradation or even failure. In contrast, supercapacitors, with their unique structural and material advantages, show higher stability and reliability under high temperature conditions, and have gradually become the mainstream energy storage solution in high-temperature environments. However, to meet higher-level application requirements, it is still necessary to further develop supercapacitors with more excellent performance and stronger high-temperature resistance.
[0004] Patent document with application number CN202211660156.3 discloses a gallium nitride / metal oxide composite electrode material and its preparation method and application, which is to obtain a porous GaN single crystal film by corroding a GaN single crystal wafer; and immerse the single crystal film in a metal salt aqueous solution to obtain a gallium nitride / metal oxide composite electrode material by hydrothermal reaction; the electrode material is mixed with a conductive agent and a binder and ground, and N-methylpyrrolidone is added to obtain a slurry, and then the slurry is coated on a current collector to obtain a working electrode for assembling a supercapacitor. This method has the following shortcomings:
[0005] First, the porous GaN film is formed into a slurry through steps such as grinding, and then the slurry is applied to the current collector to form the required electrode, so the GaN film cannot be directly used as an electrode material;
[0006] Second, the electrode preparation process is relatively complicated;
[0007] Third, since the grinding process to form a slurry cannot guarantee perfect mixing of the electrode material with other materials, and the coating process cannot guarantee that the electrode material is evenly covered on the current collector, the prepared electrode will be affected by the uncertainty brought by the complex process;
[0008] Fourthly, the electrode material prepared thereby fails to form a patterned structure, which will increase the production cost and be unfavorable for the subsequent improvement of production efficiency and wide application. Summary of the invention
[0009] The purpose of the present invention is to address the deficiencies of the above-mentioned prior art and propose a method for preparing a high-temperature resistant supercapacitor based on GaN as the electrode material, so as to reduce the complexity and cost of the electrode preparation process, improve production efficiency, and realize large-scale production and application.
[0010] The technical idea for achieving the purpose of the present invention is: to process the epitaxial gallium nitride on the Si wafer through photolithography technology to form a gallium nitride film, and then directly form the cathode and anode of the supercapacitor; to prepare the electrode material structure and high-precision patterned lines through photolithography technology to improve production efficiency and make the device performance more stable.
[0011] Based on the above technical ideas, the implementation steps of the present invention include the following:
[0012] (1) Pre-treatment of cleaning the target substrate made of GaN thin film;
[0013] (2) performing photolithography on the cleaned target substrate to obtain a patterned photoresist-target substrate structure, wherein the patterned line width is 2 to 50 μm;
[0014] ( 3) using an electron beam evaporation device to deposit a layer of metal current collector on the photoresist-target substrate structure to obtain a sample with a current collector / photoresist-target substrate structure;
[0015] (4) stripping the photoresist from the sample of the current collector / photoresist-target substrate, leaving the sample of the current collector-target substrate and performing secondary photolithography to form a photoresist-current collector-target substrate structure, and using the photoresist as a protective layer;
[0016] (5) performing ICP etching on the above-mentioned photoresist-current collector-target substrate sample, and patterning the target substrate through the protective effect of the photoresist to obtain the required positive and negative electrode regions;
[0017] (6) stripping the photoresist from the patterned photoresist-current collector-target substrate sample to obtain a patterned current collector-target substrate sample and performing annealing treatment;
[0018] (7) Leading out positive and negative electrode leads on the positive and negative electrode regions of the patterned current collector-target substrate to obtain the desired positive and negative electrodes;
[0019] (8) A drop-coated electrolyte is prepared and drop-coated on a current collector-target substrate sample with positive and negative electrodes drawn out, and then encapsulated with a layer of polydimethylsiloxane film to produce a high-temperature resistant micro supercapacitor based on GaN as the electrode material.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] First, the present invention uses photolithography technology to form a high-resolution patterned micro-supercapacitor, which is more delicate in structure and easier to integrate with other electronic components to form a high-density integrated circuit, which helps to improve the production efficiency, stability and service life of the capacitor;
[0022] Secondly, the present invention adopts the traditional semiconductor process to prepare the micro supercapacitor, which can be combined with the traditional silicon electronic device preparation process to realize the integrated preparation of the micro rectifier circuit;
[0023] Thirdly, the present invention uses GaN as the electrode material, which can realize the normal operation of the capacitor under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the structure of an existing micro supercapacitor;
[0025] Figure 2 A schematic diagram of the process of making a micro supercapacitor according to the present invention; DETAILED DESCRIPTION
[0026] The effects of specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0027] Reference Figure 1 The existing micro supercapacitor includes an insulating substrate, a current collector, and an electrode material. The three can form a sandwich structure with two different positional relationships: electrode material-current collector-insulating substrate or current collector-electrode material-insulating substrate.
[0028] Reference Figure 2The present invention provides the following three embodiments for preparing micro supercapacitors. However, the present invention is not limited thereto. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0029] Example 1: Epitaxial growth on a Si wafer with a thickness of 100 nm, doped with Si, and a doping concentration of 1×10 18 cm -3 A Ti / Au-GaN-Si micro supercapacitor with Ti / Au as the metal current collector and PVA-H2SO4 gel electrolyte as the encapsulating electrolyte was prepared on a n-GaN substrate.
[0030] Step 1: pre-treat GaN.
[0031] The epitaxial GaN on Si wafer was selected as the substrate of the overall device, and was ultrasonically cleaned several times with deionized water, analytical pure acetone, and analytical pure isopropanol, respectively, and then dried with nitrogen for later use.
[0032] Step 2: Photolithography to prepare patterned samples.
[0033] 2.1) Place the pretreated GaN-Si sample on a spinner, drip positive photoresist AZ5214 onto it, and then spin it at 600r / s for 5s to ensure that the photoresist is initially and evenly distributed on the GaN surface. Then spin it at 3000r / s for 30s to form a uniform, dense and appropriately thick film on the sample surface.
[0034] 2.2) Place the coated sample on a hot plate and dry it at 110°C for 60 seconds. 2 Exposure is performed with an exposure dose of ;
[0035] 2.3) Place the exposed photoresist-GaN sample in a developer for 30 seconds, then rinse the sample in deionized water 30 s , Dry with nitrogen to form a microelectrode line with a width of 50 μ Patterned photoresist for m- G a N-S i sample.
[0036] Step 3, depositing the current collector.
[0037] Place the patterned photoresist-GaN-Si sample into the electron beam evaporation equipment and keep the vacuum degree of the equipment ≤1*10 - 8 Torr, on the photoresist-GaN-Si sample A layer of metal current collector Ti / A with a thickness of 20 / 50 nm was deposited at a deposition rate of u, The obtained structure is metal current collector / photoresist-G a N-Si composite samples.
[0038] Step 4: perform a secondary photolithography process.
[0039] 4.1) The prepared metal current collector / photoresist-GaN-Si composite sample is subjected to a photoresist stripping treatment, thereby exposing the metal current collector with a specific pattern and the GaN substrate below, and obtaining a patterned metal current collector-GaN sample, which is specifically implemented as follows: placing the metal current collector / photoresist-GaN-Si sample in an acetone solution and gently shaking it with tweezers to strip the photoresist, and then immersing the sample in alcohol and deionized water in turn and letting it stand for 1 minute each, and then taking it out and drying it with nitrogen;
[0040] 4.2) In the secondary photolithography process, AZ5214 is selected as the photoresist. To ensure the consistency and reliability of the photolithography effect, the same parameter settings as in the above step 3 are adopted, including spin coating speed, baking temperature and time, exposure dose, etc., so that a layer of photoresist is attached to the entire metal current collector and part of the GaN substrate as a protective layer, and a metal current collector / photoresist-GaN-Si structure with a different pattern from the above sample is formed again.
[0041] Step 5, perform ICP etching to obtain an anode and a cathode.
[0042] The ICP etching method is used to etch the metal current collector / photoresist-GaN-Si sample to form grooves under the process conditions of 500W power, a Cl2 / BCl3 mixed gas etching gas, and an etching depth of at least 100nm to obtain an anode and a cathode.
[0043] Step 6, performing secondary photoresist stripping and rapid thermal annealing treatment on the sample after ICP etching.
[0044] 6.1) Place the metal current collector / photoresist-GaN-Si sample in an acetone solution and gently shake it with tweezers to peel off the photoresist. Then soak the sample in alcohol and deionized water, take it out and blow dry it with nitrogen to obtain a sample structure with a metal current collector on GaN;
[0045] 6.2) The metal current collector-GaN-Si sample was placed in a nitrogen atmosphere and subjected to rapid thermal annealing at 850° C. for 35 seconds.
[0046] Step 7, drop-coat PVA-H2SO4 gel electrolyte and make a micro supercapacitor.
[0047] 7.1) Dissolve 10 g PVA and 10 g H2SO4 solution in 80 mL deionized water to prepare an electrolyte mixed solution;
[0048] 7.2) Place the electrolyte mixture solution in a water bath heating box, set the water bath heating box to a constant temperature of 80°C, and stir and heat for 1 hour to obtain a colorless and transparent PVA-H2SO4 gel electrolyte;
[0049] 7.3) PVA-H2SO4 gel electrolyte was drop-coated on the sample surface and cured for 24 hours. The positive and negative electrode leads were drawn out and encapsulated with PDMS to obtain a micro supercapacitor Ti / Au-GaN-Si with a Ti / Au current collector, GaN electrode material, and Si insulating substrate.
[0050] Example 2: Epitaxial growth on a Si wafer with a thickness of 100 nm, doped with Si, and a doping concentration of 1×10 19 cm -3 A Ni / Au-GaN-Si micro supercapacitor with Ni / Au as the metal current collector and LiCl-gel as the encapsulating electrolyte was prepared on a n-GaN substrate.
[0051] Step 1: pre-treat GaN.
[0052] The specific implementation of this step is the same as step 1 of Example 1.
[0053] Step 2: Photolithography to prepare patterned samples.
[0054] 2-1) Place the pre-treated GaN-Si sample on a spinner, drip positive photoresist AZ5214 onto it, and then spin it at 700r / s for 5s to ensure that the photoresist is initially and evenly distributed on the GaN surface, and then spin it at 3100r / s for 30s to form a uniform, dense and appropriately thick film of photoresist on the sample surface;
[0055] 2-2) The coated sample was placed on a heating plate and dried at 110°C for 60 seconds, and then the sample was treated with a photolithography machine at 220 MJ / cm 2 Exposure is performed with an exposure dose of ;
[0056] 2-3) Place the exposed photoresist-GaN-Si sample in a developer for 30 seconds, then rinse the sample in deionized water. 30 s , Dry with nitrogen to form a microelectrode line with a width of 50 μ Patterned photoresist for m- G a N-S i sample.
[0057] Step three: depositing the current collector.
[0058] The patterned photoresist-G a The N-Si sample was placed in the electron beam evaporation equipment and the vacuum degree of the equipment was maintained at ≤1 * 10 -8 T orr, In photoresist-G a On the N-Si sample A layer with a thickness of 10 / 50 is deposited at a deposition rate of nm Metal current collector Ni / A u, The obtained structure is metal current collector / photoresist-G a N-Si composite samples.
[0059] Step 4: perform a secondary photolithography process.
[0060] 4-1) placing the metal current collector / photoresist-GaN-Si sample in an acetone solution and gently shaking it with tweezers to peel off the photoresist to expose the metal current collector with a specific pattern and the GaN substrate underneath, then soaking the sample in alcohol and deionized water in turn and letting it stand for 1 min each, taking it out and drying it with nitrogen to obtain a patterned metal current collector-GaN-Si sample;
[0061] 4-2) In the secondary photolithography process, AZ5214 is selected as the photoresist. To ensure the consistency and reliability of the photolithography effect, the same parameter settings as in the above step 2 are adopted, including spin coating speed, baking temperature and time, exposure dose, etc., so that a layer of photoresist is attached to the entire metal current collector and part of the GaN substrate as a protective layer, and a metal current collector / photoresist-GaN-Si structure with a different pattern from the above sample is formed again.
[0062] Step five, performing ICP etching on the metal current collector / photoresist-GaN-Si sample to obtain a cathode and an anode.
[0063] The specific implementation of this step is the same as step 5 of Example 1.
[0064] Step six, stripping the photoresist and performing rapid thermal annealing on the sample after ICP etching.
[0065] The specific implementation of this step is the same as step 6 of Example 1.
[0066] Step seven, drop-coat LiCl-gel electrolyte and make a micro supercapacitor.
[0067] 7-1) dissolving LiCl salt in deionized water to form a LiCl aqueous electrolyte with a concentration of 20 mol / L;
[0068] 7-2) Mixing 20 mol / L of LiCl aqueous electrolyte with 6 wt% SiO2 powder with a particle diameter of 0.007 mm to form a LiCl-gel electrolyte;
[0069] 7-3) LiCl-gel electrolyte was drop-coated on the sample surface and cured for 24 hours, and the positive and negative electrode leads were drawn out and encapsulated with PDMS to obtain a micro supercapacitor Ni / Au-GaN-Si with a current collector of Ni / Au, an electrode material of GaN, and an insulating substrate of Si.
[0070] Example 3: Epitaxial growth on a Si wafer with a thickness of 100 nm, doped with Si, and a doping concentration of 1×10 17 cm -3 A Ti / Al-GaN-Si micro supercapacitor with Ti / Al as the metal current collector and EG-LiCl mixed gel electrolyte as the encapsulating electrolyte was prepared on a n-GaN substrate.
[0071] Step A: pre-treating the GaN substrate.
[0072] The specific implementation of this step is the same as step 1 of Example 1.
[0073] Step B, photolithography to prepare patterned samples.
[0074] B1) placing the pre-treated GaN-Si sample on a spinner, dripping positive photoresist AZ5214 on it, spinning it at a speed of 500 r / s for 5 seconds to ensure that the photoresist is initially and evenly distributed on the GaN-Si surface, and then spinning it at a speed of 3200 r / s for 30 seconds to form a uniform, dense and appropriately thick film of the photoresist on the sample surface;
[0075] B2) Place the coated sample on a hot plate and dry it at 110°C for 60 seconds. Then use a photolithography machine to dry it at 210 MJ / cm 2 Exposure is performed with an exposure dose of ;
[0076] B3) Place the exposed photoresist-GaN-Si sample in a developer for 30 seconds, then rinse the sample in deionized water 30 s , Dry with nitrogen to form a microelectrode line with a width of 50 μ Patterned photoresist for m- G a N-S i sample.
[0077] Step C, depositing the current collector.
[0078] Place the patterned photoresist-GaN-Si sample into the electron beam evaporation equipment and keep the vacuum degree of the equipment ≤1*10-8 Torr, on the photoresist-GaN-Si sample A layer of metal current collector Ti / Al with a thickness of 20 / 80 nm was deposited at a deposition rate of , The obtained structure is metal current collector / photoresist-G a N-Si composite samples.
[0079] Step D, performing secondary photolithography on the metal current collector / photoresist-GaN-Si sample.
[0080] D1) placing the metal current collector / photoresist-GaN-Si sample in an acetone solution and gently shaking it with tweezers to peel off the photoresist to expose the metal current collector with a specific pattern and the GaN substrate underneath, then soaking the sample in alcohol and deionized water in turn and letting it stand for 1 min each, taking it out and drying it with nitrogen to obtain a patterned metal current collector-GaN-Si sample;
[0081] D2) To ensure the consistency and reliability of the two photolithography effects, AZ5214 was selected as the photoresist, and the same parameter settings as in the above step B were adopted, including spin coating speed, baking temperature and time, exposure dose, etc., so that a layer of photoresist was attached to the entire metal current collector and part of the GaN substrate as a protective layer, and a metal current collector / photoresist-GaN-Si structure with a different pattern from the above sample was formed again.
[0082] Step E: ICP etching of the metal current collector / photoresist-GaN-Si sample
[0083] The specific implementation of this step is the same as step 5 of Example 1.
[0084] Step F, stripping the photoresist and performing rapid thermal annealing on the sample after ICP etching.
[0085] The specific implementation of this step is the same as step 6 of Example 1.
[0086] Step H, drop coating of EG-LiCl mixed gel electrolyte and fabrication of micro supercapacitors.
[0087] H1) 4.239 g of anhydrous LiCl was mixed with an EG-water binary sol having an EG volume fraction of 50% to form an electrolyte having a LiCl concentration of 10 mol / L;
[0088] H2) adding 1 g of polyvinyl alcohol to the above electrolyte and continuing to stir at 90° C. for 10 h to obtain a uniform gel electrolyte;
[0089] H3) EG-LiCl mixed gel electrolyte was drop-coated on the sample surface and cured for 24 hours, and the positive and negative electrode leads were drawn out and encapsulated with PDMS to obtain a micro supercapacitor Ti / Al-GaN-Si with a current collector of Ti / Al, an electrode material of GaN, and an insulating substrate of Si.
[0090] The above descriptions are only several specific examples of the present invention and do not constitute a limitation on the scope of the present invention. It should be pointed out that, for those skilled in the art, without departing from the concept of the present invention, several variations and improvements in form and detail can be made, for example, in addition to the PVA-H2SO4, LiCl-gel gel electrolyte and EG-LiCl mixed gel electrolyte used in the specific embodiments, other acid-base gel electrolytes, salt-in-water and ionic liquid gel electrolytes can also be used, but these modifications and changes based on the concept of the present invention are still within the scope of the claims of the present invention.
Claims
1. A method for preparing a high temperature resistant supercapacitor based on GaN as an electrode material, characterized in that: The steps include: (1) Pre-treatment of cleaning the target substrate made of GaN thin film; (2) performing photolithography on the cleaned target substrate to obtain a patterned photoresist-target substrate structure, wherein the patterned line width is 2 to 50 μm; (3) using an electron beam evaporation device to deposit a layer of metal current collector on the photoresist-target substrate structure to obtain a sample with a current collector / photoresist-target substrate structure; (4) stripping the photoresist from the sample of the current collector / photoresist-target substrate, leaving the sample of the current collector-target substrate and performing secondary photolithography to form a photoresist-current collector-target substrate structure, and using the photoresist as a protective layer; (5) performing ICP etching on the above-mentioned photoresist-current collector-target substrate sample, and patterning the target substrate through the protective effect of the photoresist to obtain the required positive and negative electrode regions; (6) stripping the photoresist from the patterned photoresist-current collector-target substrate sample to obtain a patterned current collector-target substrate sample and performing annealing treatment; (7) Leading out positive and negative electrode leads on the positive and negative electrode regions of the patterned current collector-target substrate to obtain the desired positive and negative electrodes; (8) A drop-coated electrolyte is prepared and drop-coated on a current collector-target substrate sample with positive and negative electrodes drawn out, and then encapsulated with a layer of polydimethylsiloxane film to produce a high-temperature resistant micro supercapacitor based on GaN as the electrode material.
2. The method according to claim 1, characterized in that In step (1), the pretreatment for cleaning the target substrate made of GaN thin film is to use deionized water, analytical pure acetone, and analytical pure isopropanol in sequence, ultrasonically clean them for 2 minutes respectively, and blow dry them with nitrogen.
3. The method according to claim 1, characterized in that Step (2) performs photolithography on the cleaned target substrate, and the process flow is as follows: (2a) using positive glue drop coating on the target substrate, and placing the substrate on a glue spinner and first spin coating at a low speed of 500-1000 r / s for 3s-6s, and then spin coating at a high speed of 2800r / s-3000r / s for 25s-30s to complete the glue coating; (2b) placing the coated target substrate on a hot plate and pre-baking it at 90° C. to 120° C. for 40 seconds to 90 seconds; (2c) Place the treated target substrate in a photolithography machine and use an interdigital mask to irradiate the substrate at 180 MJ / cm 2 -230MJ / cm 2 Exposure is performed at an exposure dose; (2d) The exposed sample was immersed in developer and deionized water for 30 seconds each, and finally dried with nitrogen gas.
4. The method according to claim 1, characterized in that: Step (3) depositing a metal current collector layer on the photoresist-target substrate structure using an electron beam evaporation device, wherein the parameters are set to: maintain the vacuum degree of the electron beam evaporation device ≤ 1*10 - 8 Torr, the deposition rate is 5. The method according to claim 1, characterized in that Step (4) performs a photoresist stripping process on the sample of the current collector / photoresist-target substrate, and the implementation steps include the following: First, place the current collector / photoresist-target substrate sample in an acetone solution and shake it gently to peel off the photoresist; The sample after stripping the photoresist was then immersed in alcohol and deionized water for 1 min each, taken out and dried with nitrogen to obtain a current collector-target substrate sample.
6. The method according to claim 1, characterized in that In step (4), the sample of the current collector-target substrate is subjected to secondary photolithography, and the implementation steps include the following: (4a) using a positive resin drop coating on the above-mentioned photoresist-target substrate sample, and placing the substrate on a spin coating machine at a low speed of 500r / s-1000r / s for 3s-6s, and then at a high speed of 2800r / s-3000r / s for 25s-30s to complete the coating; (4b) placing the coated sample on a hot plate and pre-baking it at 90° C. to 120° C. for 40 seconds to 90 seconds; (4c) Place the treated sample in a photolithography machine and use a secondary photolithography mask at 180 MJ / cm 2 -230MJ / cm 2 Exposure is performed at an exposure dose; (4d) The exposed sample was immersed in developer and deionized water for 30 seconds each, and finally dried with nitrogen gas.
7. The method according to claim 1, characterized in that In step (5), the sample of photoresist-current collector-target substrate is subjected to ICP etching, and the etching parameters include the following: The ICP power adopted is 500W. The etching gas is a mixture of Cl2 / BCl3. Etching depth ≥100nm.
8. The method according to claim 1, characterized in that: The drop-coated electrolyte configured in step (8) includes: PVA-H2SO4 gel electrolyte, LiCl-gel gel electrolyte, and EG-LiCl mixed gel electrolyte.
9. The method according to claim 8, characterized in that: The PVA-H2SO4 gel electrolyte has the following configuration steps: (8a) 10 g of PVA and 10 g of H2SO4 solution were dissolved in 80 mL of deionized water to prepare an electrolyte mixed solution; (8b) placing the electrolyte mixture solution in a water bath heating box, setting the constant temperature of the water bath heating box to 80° C., stirring and heating for 1 h, and obtaining a colorless and transparent PVA-H2SO4 gel electrolyte; The LiCl-gel electrolyte has the following steps for preparation: (8c) dissolving LiCl salt in deionized water to form a LiCl aqueous electrolyte with a concentration of 20 mol / L; (8d) 20 mol / L LiCl aqueous electrolyte was mixed with 6 wt% SiO2 powder with a particle diameter of 0.007 mm to form a LiCl-gel electrolyte; The EG-LiCl mixed gel electrolyte has the following steps for preparation: (8e) 4.239 g of anhydrous LiCl was mixed with an EG-water binary sol having an EG volume fraction of 50% to form an electrolyte having a LiCl concentration of 10 mol / L; (8f) 1 g of polyvinyl alcohol was added to the above electrolyte and stirred at 90 °C for 10 h to obtain a uniform EG-LiCl mixed gel electrolyte.
Citation Information
Patent Citations
Gallium nitride / metal oxide composite electrode material and preparation method and application thereof
CN116230413A